SHIFTING TO HYBRID LEARNING;WHAT DO RURAL ENGLISH TEACHERS NEED ? - Utin Nadila Nadila; Dedi Irwan; M. Iqbal Ripo Putra (XXXX-XXXX, 2022)
This research focuses on Shifting to hybrid learning; what do rural English teachers need?, how is the learning system during hybrid learning, to illustrate the difficulties in achieving successful learning practices with limited time in several schools in Kapuas Hulu. The method used is a descriptive qualitative approach. The data collection technique is direct communication. The data collection tool is an interview using an interview guide. The schools are SMAN 01, SMPN 02, and MTS Hidayatul Mustaqim Bunut Hulu. The data analysis technique is to make a transcript in the form of text from the interview results. The results of the study are, there is not much that teachers can do in the learning system during the hybrid learning period. From the results of research in 3 schools where teachers have difficulty implementing hybrid learning. Some of the problems experienced by teachers are about the learning media, the learning media used are only books / worksheets, besides that the lack of science and technology knowledge from teachers and attention from schools causes the application of hybrid learning to experience problems, especially during online learning, lack of awareness from students in utilizing hybrid applications. During the pandemic, the role of parents is very important in reminding students. Therefore, what English teachers need in the application of hybrid learning learning is English teacher training regarding learning media and other supporting facilities, collaboration between schools and parents to realize more effective hybrid learning learning, and support from the government to simplify the material. The researcher hopes that it can be a solution for the future, especially during the pandemic. In order to meet the needs of teachers in difficult times, because the needs of teachers also need attention so that practical learning can still be carried out effectively.